"They're kept in a bubble": Healthcare professionals' views on transitioning young adults with congenital heart disease from paediatric to adult care. (7th June 2018) - McLoughlin, A.; Matthews, C.; Hickey, T. M.
Abstract: Background: Due to medical advances, growing numbers of adolescents with congenital heart disease (CHD) survive into adulthood and transferring from paediatric to adult healthcare. This transfer is significant step in a young person's life, and this study examines the views of Irish healthcare professionals' on how best to manage this transition. Methods: Purposeful sampling was used to invite participation by healthcare professionals (HCPs) from a variety of disciplines whose caseloads include adolescents and young adults with CHD. Fourteen professionals participated in semistructured interviews regarding their experiences of the transition process and their recommendations. Data were collected during Spring 2016 and analysed using thematic analysis. Results: Results indicated that the current approach to transition and transfer could be improved. Professionals identified barriers hindering the transition process such as cultural and attitudinal differences between HCPs dealing with child and adult patients, inadequate preparation and education of patients about their condition, parental reluctance to transfer, and concern about parents' role in on‐going treatment. Measures such as better support and education for both the patients and their parents were recommended, in order to facilitate a smoother transition process for all parties involved. Additionally, HCPs identified the need for better collaboration and communication, both between paediatric and adult healthcare professionals and between hospitals, to ensure greater continuity of care for patients. Conclusions: Action is required in order to improve the current transition process. Measures need to be taken to address the barriers that currently prevent a smooth transition process for young adult CHD patients. Professionals recommended the implementation of a structured transition clinic to deal with the wide variety of needs of transitioning adolescent patients and their families. Recommendations for future research are also made.